Assessing the effectiveness of Environmental Impact Assessment as a safeguard to biodiversity in the Cape Floristic Region of South Africa - Nortje, Griffin (Department of Environmental and Geographical Science, 2018)
Environmental Impact Assessment (EIA) is subject to challenges that undermine this process as an effective safeguard to biodiversity. Internationally, effective EIA is hindered by the following issues: a low priority assigned to the consideration of biodiversity and a limited capacity to carry out assessments; a lack of formalised procedures and inconsistent methodologies to address biodiversity within the EIA framework; and a lack of formal requirements for post-project monitoring of biodiversity aspects. Traditionally effectiveness studies in this regard have focused on evaluating the procedural aspects of EIA, and have focused less on the substantive outcomes of the post-authorisation phase of a proposed project. While South Africa has a considerable body of literature pertaining to the procedural aspects of EIA, there remain two substantial gaps in the literature. Firstly, there is an evident absence of effectiveness studies in South Africa that focus primarily on biodiversity-specific procedure. Secondly, almost no research has been conducted in South Africa which investigates the outcomes of mitigation measures, mandatory monitoring, reporting and compliance with biodiversity aspects of EIA. This research therefore aims to fill these gaps by investigating the quality of information generated in five EIAs in the Western Cape. It also examines the implementation success of mitigation measures aimed at managing unavoidable impacts in the post-authorisation phase of these projects. This research has adopted a case study methodological approach. Five EIAs were selected from a sample of 9. In no order of significance, the variables considered most important in the sampling protocol were: the presence of a biodiversity-related specialist report; availability of environmental assessment documentation; overall cases to represent at least two different local jurisdictions; and the uniqueness of adopted biodiversity-related mitigation measures. The primary method used to evaluate the quality of biodiversity-related information is a Key Performance Indicator analysis, whereby the performance of cases is measured against legal and best-practice reporting principles. The substantive outcomes of EIA have been investigated by means of site inspections and interviews with key stakeholders. This research has found that the five cases performed well with complying with best-practice EIA procedure, indicating a 53% full compliance, 29% partial compliance and 18% of best-practice principles were not complied with at all. This research has shown that direct impacts on biodiversity (such as the physical removal of indigenous vegetation) are adequately identified, and indirect impacts (typically those impacting off-site and on ecological processes) are poorly identified in EIA. Therefore, the information required to avoid impacts on biodiversity is available, but this research has found that it is underutilized in this regard. Notably, avoidance of impacts was undermined inadequate site and layout alternatives and poor decision making in terms of the regular authorisation of irreversible impacts on biodiversity. Conversely, only 18% of mitigation measures were fully complied with, 36% were partially complied with, and 45% of mitigation measures were not complied with. These results indicate a poor performance of EIA in the implementation stage of a project lifecycle. This research has concluded this is most likely due to a poor conversion of recommended mitigation measures into conditions of authorisation and a limited capacity of the competent authority to perform compliance monitoring.